Stabilizing networks? Social organizations and old-age services in urban communities in China - Bingqin Li; Lijie Fang; Bo Hu (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper examines the characteristics of old-age services, and show that delivering social services involves a complex system that can only be achieved with the participation and coordination of multiple stakeholders. This means that the system is unavoidably a network of stakeholders, comprising actors in both formal and informal sectors. It is then discussed the theories of network transition and established an analytical framework to understand the process of adjustment after new actors join an existing network. The paper analyzes six cities in China to examine which factors help a city adapt to changes more effectively. In the conclusion, with reference to the experience of these Chinese cities, it is discussed the current state of the network stabilization process in different contexts and explore the research outcomes. This research contributes to understanding network transition by establishing the role of community features.
Keywords: 330